Credit Environment and Small Business Dynamics: Evidence from Establishment-Level Data. Issue 2 (2nd November 2022) - Lin, Chen; Tai, Mingzhu; Xie, Wensi
Abstract: We evaluate how a positive, technology-driven shock to bank liquidity affects small business dynamics across different size distributions. We first show that banks receiving positive liquidity shocks increase lending to relatively larger SMEs, not to the smallest firms. This finding is consistent with the view that a positive liquidity shock enhances bank charter values, thereby reducing risk-taking incentives. Moreover, such disproportionate credit allocation leads to a crowding-out effect on micro firms. When larger SMEs grow faster and exit less because of better access to credit, their expansion stifles the development of micro firms, whose access to credit remains unchanged. ( JEL G21, J21, L22)